620MPa-grade ultralow-hydrogen-coating low-alloy steel welding rod for generator set, preparation method of 620MPa-grade ultralow-hydrogen-coating low-alloy steel welding rod and deposited metal

By using specific chemical compositions in the welding rod, the mechanical properties of the weld metals of the welding rod are improved, the problem of insufficient mechanical properties of the existing welding rods is solved, and the localization of the welding rods is realized, reducing costs and procurement risks.

CN119857960AActive Publication Date: 2025-04-22ATLANTIC CHINA WELDING CONSUMABLES
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411984873.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-04-22
Estimated Expiration
2044-12-31

AI Technical Summary

Technical Problem

The mechanical properties of the existing welding rods are difficult to meet the construction needs of my country's nuclear power projects. In addition, foreign welding rods are expensive, communication and supervision are difficult during the production process, long production cycles, and procurement risks are high.

Method used

A 620MPa grade low alloy steel welding rod for ultra-low hydrogen sterilization of generator sets is provided. The chemical components of the sterilization include dolomite, lithium carbonate, barium carbonate, lithotridium sulfide, fluorite, ferrosilicon, nickel powder, ferromolybdenum, metal chromium, potassium fluoroborate, aluminum magnesium alloy, sodium alginate and soda ash, and welding rods and deposited metals are prepared by specific preparation methods.

Benefits of technology

It improves the mechanical properties of the welded metal of the welding rod, meets the high requirements of the generator set, and realizes the localization of the welding rod, reducing costs and procurement risks.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119857960A_ABST
    Figure CN119857960A_ABST
Patent Text Reader

Abstract

The invention relates to a 620 MPa-grade ultralow-hydrogen-coating low-alloy steel welding rod for a generator set, a preparation method of the 620 MPa-grade ultralow-hydrogen-coating low-alloy steel welding rod and deposited metal, and belongs to the technical field of welding. The coating comprises the following chemical components: dolomite, lithium carbonate, barium carbonate, magnesia, fluorite, ferrosilicon, nickel powder, ferromolybdenum, chromium metal, potassium fluoborate, aluminum magnesium alloy, sodium alginate and sodium carbonate; the invention relates to a high-strength wear-resistant steel plate which is prepared from the following components in parts by mass: 100 to 200 parts of dolomite, 100 to 150 parts of lithium carbonate, 100 to 200 parts of magnesia, 300 to 350 parts of fluorite, 100 to 150 parts of silicon iron, 10 to 20 parts of nickel powder, 10 to 20 parts of ferromolybdenum, 5 to 10 parts of chromium metal and 1 to 3 parts of aluminum-magnesium alloy. The welding rod has excellent mechanical properties, the electric arc is stable during welding of the welding rod, the appearance is attractive, the anti-cracking performance of deposited metal of the welding rod is good, and weld metal has chemical components and mechanical properties equivalent to those of steel.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of welding technology, and in particular to a 620MPa-grade low-alloy steel welding rod with an ultra-low hydrogen coating for a generator set, a preparation method thereof, and a deposited metal. Background Art

[0002] The welding rods are mainly used for welding of steam and feed water circuit equipment steel in conventional nuclear power islands and feed water pipelines, high-pressure heaters and other components of high-parameter thermal power generation equipment.

[0003] However, the mechanical properties of the deposited metal of the current welding rod are difficult to meet the construction needs of my country's nuclear power projects and realize the localization of the welding rod. In addition, foreign welding rods are expensive, communication and supervision during the production process are difficult, the production cycle is long, and the procurement risk is high. Summary of the invention

[0004] The present application provides a 620MPa-grade low-alloy steel welding rod with ultra-low hydrogen coating for a generator set, a preparation method thereof, and a deposited metal to solve the following technical problem: how to improve the mechanical properties of the deposited metal of the welding rod.

[0005] In the first aspect, the embodiment of the present application provides a 620MPa-level low-alloy steel welding rod with an ultra-low hydrogen coating for a generator set, the welding rod comprising a welding core and a coating coated on at least a portion of the surface of the welding core, the chemical composition of the coating comprising: dolomite, lithium carbonate, barium carbonate, magnesia, fluorite, ferrosilicon, nickel powder, ferromolybdenum, metallic chromium, potassium fluoroborate, aluminum-magnesium alloy, sodium alginate and soda ash; wherein, in parts by mass,

[0006] Dolomite is 100 to 200 parts, lithium carbonate is 100 to 150 parts, magnesite is 100 to 200 parts, fluorite is 300 to 350 parts, ferrosilicon is 100 to 150 parts, nickel powder is 10 to 20 parts, ferromolybdenum is 10 to 20 parts, metallic chromium is 5 to 10 parts, and aluminum-magnesium alloy is 1 to 3 parts.

[0007] Optionally, the barium carbonate is 200 to 300 parts, the potassium fluoroborate is 1 to 4 parts, the sodium alginate is 1 to 15 parts, and the soda ash is 5 to 10 parts.

[0008] Optionally, the chemical composition of the welding core includes: carbon, manganese, silicon, nickel, molybdenum, chromium, niobium, copper, sulfur, phosphorus, and matrix element Fe; wherein, in parts by mass,

[0009] Carbon is 0.07 to 0.12 parts, manganese is 0.90 to 1.50 parts, silicon is 0.05 to 0.10 parts, nickel is 0.50 to 1.00 parts, molybdenum is 0.01 to 0.10 parts, chromium is 0.01 to 0.10 parts, niobium is 0.01 to 0.10 parts, copper is 0.50 to 0.70 parts, sulfur is 0.001 to 0.005 parts, and phosphorus is 0.001 to 0.007 parts.

[0010] In a second aspect, an embodiment of the present application provides a method for preparing the welding rod according to any one of the embodiments of the first aspect, the preparation method comprising:

[0011] Mixing the coating powder with the binder to obtain a mixed material;

[0012] The mixed material is sequentially subjected to a first baking, a second baking and cooling to obtain a welding rod; wherein the temperature of the first baking is 85°C to 90°C, and the temperature of the second baking is 380°C to 400°C.

[0013] Optionally, the weight of the binder is 20% to 30% of the weight of the coating powder.

[0014] Optionally, the cooling end point temperature is ≤50°C.

[0015] In a third aspect, an embodiment of the present application provides a 620 MPa grade cladding metal for welding a low alloy steel electrode with an ultra-low hydrogen coating for a generator set, wherein the cladding metal is obtained by the electrode described in any one of the first aspects during the welding process.

[0016] Optionally, the chemical composition of the deposited metal includes: carbon, manganese, silicon, nickel, molybdenum, chromium, niobium, copper, boron, aluminum, magnesium, sulfur, phosphorus, and matrix element Fe; wherein, in parts by mass,

[0017] Carbon is 0.07 to 0.12 parts, manganese is 0.90 to 1.50 parts, silicon is 0.15 to 0.30 parts, nickel is 0.80 to 1.40 parts, molybdenum is 0.30 to 0.60 parts, chromium is 0.10 to 0.30 parts, niobium is 0.01 to 0.10 parts, copper is 0.50 to 0.70 parts, boron is 0.0001 to 0.003 parts, aluminum is 0.0001 to 0.010 parts, magnesium is 0.0001 to 0.010 parts, sulfur is 0.001 to 0.005 parts, and phosphorus is 0.001 to 0.007 parts.

[0018] Optionally, the diffusible hydrogen of the deposited metal is 0.5 ml / 100 g to 4.0 ml / 100 g, and the water content of the coating of the welding rod is 0.05% to 0.15%.

[0019] Optionally, the deposited metal satisfies the following mechanical properties: room temperature tensile strength of the weld is 620MPa~800MPa, room temperature yield strength is 530MPa~700MPa, room temperature elongation after break is 18%~35%, high temperature tensile strength of the weld at 400℃ is ≥500MPa, 0℃ impact single value is ≥100J, -40℃ impact single value is ≥60J, and the ductile-brittle transition temperature of the drop hammer test is ≤-10℃.

[0020] The above technical solution provided by the embodiment of the present application has the following advantages compared with the prior art:

[0021] The 620MPa-level low-alloy steel welding rod with ultra-low hydrogen coating for a generator set provided in an embodiment of the present application comprises: dolomite, lithium carbonate, barium carbonate, magnesia, fluorite, ferrosilicon, nickel powder, ferromolybdenum, metallic chromium, potassium fluoroborate, aluminum-magnesium alloy, sodium alginate and soda ash; wherein, by weight, fluorite can reduce the content of diffusible hydrogen in the weld metal of the welding rod, and the GaF of fluorite in welding 2 With H 2 O reacts to form GaO and HF gas. GaO can increase the basicity of slag, and the escape of HF gas can reduce the content of diffusible hydrogen in the weld metal of the electrode. Dolomite and magnesia can increase the basicity of the coating while building slag and generating gas. The slag can purify impurity elements such as S and P in the weld. The CO produced 2 Gas can be used to protect the weld. Increasing the slag basicity and reducing the diffusible hydrogen content of the deposited metal can improve the crack resistance of the weld. Reducing impurity elements such as S and P in the weld can improve the weld strength and low-temperature impact toughness, and can also further improve the weld crack resistance. Lithium carbonate can produce protective gas CO 2 and a small amount of slag, which can stabilize the arc during welding. Because dolomite and magnesia react violently during welding with electrodes, the large amount of gas released has caused the molten pool to react violently and the molten pool to form poorly. Therefore, aluminum-magnesium alloy can reduce the molten pool temperature, which is beneficial to the weld formation and can obtain the target alloy composition of the weld; ferrosilicon is beneficial to the beautiful weld formation, and ferrosilicon can also deoxidize, reduce the oxygen content of the weld, and improve the mechanical properties of the weld; nickel powder, ferromolybdenum and metallic chromium can also improve the mechanical properties of the weld; barium carbonate, potassium fluoroborate , sodium alginate and soda ash are used as auxiliary agents to give full play to their role in welding and improve the mechanical properties of the weld; at the same time, dolomite is 100 to 200 parts, lithium carbonate is 100 to 150 parts, magnesite is 100 to 200 parts, fluorite is 300 to 350 parts, ferrosilicon is 100 to 150 parts, nickel powder is 10 to 20 parts, ferromolybdenum is 10 to 20 parts, metallic chromium is 5 to 10 parts, and aluminum-magnesium alloy is 1 to 3 parts, thereby improving the mechanical properties of the deposited metal of the electrode. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] The accompanying drawings, which are incorporated in and constitute a part of this specification, illustrate embodiments consistent with the present application and, together with the description, serve to explain the principles of the present application.

[0023] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, for ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative labor.

[0024] Figure 1 A schematic flow chart of a method for preparing a welding rod provided in an embodiment of the present application. DETAILED DESCRIPTION

[0025] In order to make the purpose, technical solution and advantages of the embodiments of the present application clearer, the technical solution in the embodiments of the present application will be clearly and completely described below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of this application.

[0026] Various embodiments of the present application may be presented in the form of a range; it should be understood that the description in the form of a range is only for convenience and brevity, and should not be understood as a rigid limitation on the scope of the present application; therefore, the range description should be considered to have specifically disclosed all possible sub-ranges and single numerical values ​​within the range. For example, the range description from 1 to 6 should be considered to have specifically disclosed sub-ranges, such as from 1 to 3, from 1 to 4, from 1 to 5, from 2 to 4, from 2 to 6, from 3 to 6, etc., as well as single numbers within the range, such as 1, 2, 3, 4, 5 and 6, which apply regardless of the range. In addition, whenever a numerical range is indicated herein, it is meant to include any cited number (fractional or integer) within the indicated range.

[0027] In the present application, unless otherwise specified, the directional words used, such as "upper" and "lower", refer specifically to the directions of the drawings in the accompanying drawings. In addition, in the description of the present application specification, the terms "include", "comprise", etc., mean "including but not limited to". In this article, relational terms such as "first" and "second", etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. "Parts" such as parts by weight, parts by mass, etc. represent the proportional relationship between the components. Unless otherwise specified, the various raw materials, reagents, instruments and equipment used in this application can be purchased on the market or prepared by existing methods.

[0028] In the first aspect, the embodiment of the present application provides a 620MPa-level low-alloy steel welding rod with an ultra-low hydrogen coating for a generator set, the welding rod comprising a welding core and a coating coated on at least a portion of the surface of the welding core, the chemical composition of the coating comprising: dolomite, lithium carbonate, barium carbonate, magnesia, fluorite, ferrosilicon, nickel powder, ferromolybdenum, metallic chromium, potassium fluoroborate, aluminum-magnesium alloy, sodium alginate and soda ash; wherein, in parts by mass,

[0029] Dolomite is 100 to 200 parts, lithium carbonate is 100 to 150 parts, magnesite is 100 to 200 parts, fluorite is 300 to 350 parts, ferrosilicon is 100 to 150 parts, nickel powder is 10 to 20 parts, ferromolybdenum is 10 to 20 parts, metallic chromium is 5 to 10 parts, and aluminum-magnesium alloy is 1 to 3 parts.

[0030] In the embodiment of the present application, dolomite can be 100 to 200 parts, so that dolomite can give full play to its role in slag formation and basicity adjustment during welding. The main components of dolomite are calcium carbonate and magnesium carbonate, which decompose to produce carbon dioxide gas and alkaline oxides at high welding temperatures. An appropriate amount of dolomite can ensure sufficient gas protection for the weld, while increasing the slag basicity, so that the slag can better cover the molten pool, prevent harmful gases from invading the molten pool, and avoid defects such as pores in the weld. Exemplarily, the dolomite can be 100 parts, 120 parts, 140 parts, 160 parts, 180 parts, 200 parts, etc.

[0031] The lithium carbonate can be 100 to 150 parts. The lithium carbonate content is relatively high, which makes an important contribution to reducing the diffusible hydrogen content of the weld metal. Its content range ensures that it can effectively react with hydrogen or change the metallurgical reaction conditions of the molten pool to reduce the absorption of hydrogen. In addition, lithium carbonate will also have a certain impact on the performance of the slag. The appropriate content helps the slag maintain good fluidity and coverage. Exemplarily, the lithium carbonate can be 100 parts, 110 parts, 120 parts, 130 parts, 140 parts, 150 parts, etc.

[0032] The content of magnesite can be 100 to 200 parts. The main component of magnesite is magnesium oxide. This content range helps to further improve the slag basicity. High-basicity slag is conducive to purifying impurity elements in the weld, such as reacting with impurities such as sulfur and phosphorus to reduce their content in the weld, thereby improving the strength and low-temperature impact toughness of the weld and enhancing the crack resistance of the weld. At the same time, magnesite also participates in the slag-making process and forms a slag with good performance together with other components.

[0033] Fluorite can be 300 to 350 parts. The main component, calcium fluoride, decomposes and reacts with water during welding to generate calcium oxide and hydrogen fluoride gas. A large amount of fluorite can more effectively reduce the diffusible hydrogen content of the deposited metal and increase the slag basicity. Calcium oxide can improve the properties of the slag, and the discharge of hydrogen fluoride gas plays a key role in reducing the risk of hydrogen-induced cracks in the weld. Exemplarily, the fluorite can be 300 parts, 310 parts, 320 parts, 330 parts, 340 parts, 350 parts, etc.

[0034] Ferrosilicon can be 100 to 150 parts. As a deoxidizer, ferrosilicon can effectively combine with oxygen in the weld within this content range to reduce the oxygen content in the weld. Sufficient ferrosilicon can prevent defects such as pores from appearing in the weld, and the silicon element can improve the mechanical properties of the weld. At the same time, ferrosilicon may also have a certain effect on the performance of the slag and the weld formation, helping to obtain a weld with a good appearance. Exemplarily, the ferrosilicon can be 100 parts, 110 parts, 120 parts, 130 parts, 140 parts, 150 parts, etc.

[0035] Nickel powder can be 10 to 20 parts, ferromolybdenum can be 10 to 20 parts, and metal chromium can be 5 to 10 parts. The addition amount of these alloy elements is relatively small, but the effect is significant. Nickel powder can improve the toughness and crack resistance of weld metal, especially for some welding structures that require good low-temperature toughness. Ferromolybdenum can refine the weld grains, improve the strength and tempering softening resistance of the weld, and enhance the performance of the weld at high temperatures. Metal chromium can improve the oxidation resistance and corrosion resistance of the weld metal, and work together with other alloy elements to improve the organization and performance of the weld, such as improving hardness and wear resistance. Exemplarily, the nickel powder can be 10 parts, 12 parts, 14 parts, 16 parts, 18 parts, 20 parts, etc.; ferromolybdenum can be 10 parts, 12 parts, 14 parts, 16 parts, 18 parts, 20 parts, etc.; metal chromium can be 5 parts, 6 parts, 7 parts, 8 parts, 9 parts, 10 parts, etc.

[0036] The aluminum-magnesium alloy can be 1 to 3 parts. Although the aluminum-magnesium alloy has a small content, aluminum and magnesium can both play a role in deoxidation and slag formation during welding. Aluminum can also combine with nitrogen to reduce the nitrogen content in the weld, while magnesium can improve the properties of the slag and help improve the quality of the weld. Exemplarily, the aluminum-magnesium alloy can be 1 part, 2 parts, 3 parts, etc.

[0037] Moreover, the combination of the above-mentioned composition ratios enables the coating to have good melting characteristics and stability during the welding process. For example, components such as dolomite, magnesia and fluorite ensure the formation and fluidity of slag, so that the slag can effectively cover the molten pool during welding, and the gas generation is relatively stable, and the welding operation will not be affected by excessive or insufficient reaction. Components such as ferrosilicon and aluminum-magnesium alloy help control the reaction degree of the molten pool, making the temperature and fluidity of the molten pool easier to control, thereby ensuring the smooth progress of the welding process, whether it is flat welding, vertical welding or welding in other positions, can obtain better process effects.

[0038] From the perspective of the mechanical properties of the weld, the deoxidation effect of ferrosilicon, the improvement of toughness by alloying elements such as nickel powder, and the improvement of strength and special properties (such as high temperature resistance and oxidation resistance) by ferromolybdenum and metallic chromium work together to give the weld good comprehensive mechanical properties. From the perspective of chemical composition, these component ratios can effectively control the content of impurities such as oxygen, hydrogen, sulfur, and phosphorus in the weld, and can accurately add the required alloying elements to the weld so that the chemical composition of the weld matches well with the parent material. In terms of appearance quality, the good performance of the slag and appropriate welding process parameters (thanks to the reasonable design of the component ratio) can make the weld beautiful and have good slag removal, reducing the workload of subsequent weld cleaning.

[0039] In some embodiments, the barium carbonate is 200 parts to 300 parts, the potassium fluoroborate is 1 part to 4 parts, the sodium alginate is 1 part to 15 parts, and the soda ash is 5 parts to 10 parts.

[0040] In the embodiment of the present application, the content of barium carbonate can be 200 to 300 parts, which can improve the fluidity and slag removal of slag: barium carbonate can significantly improve the fluidity of slag during welding. When the content is in the range of 200 to 300 parts, it can make the slag cover the surface of the molten pool more smoothly. Appropriate slag fluidity can ensure the smooth progress of the welding process. For example, when welding complex shapes or different welding positions (such as vertical welding and overhead welding), good slag fluidity can prevent uneven slag flow and affect the welding quality. At the same time, barium carbonate also helps to improve the slag removal of slag, so that after welding is completed, the slag is easier to fall off the surface of the weld, reducing the difficulty of cleaning the weld. By improving the slag performance, barium carbonate indirectly improves the quality of the weld. Good slag coverage can effectively isolate the air, prevent harmful gases such as oxygen and nitrogen in the air from entering the molten pool, and reduce the possibility of defects such as pores and oxidation in the weld. For example, the barium carbonate may be 200 parts, 220 parts, 240 parts, 260 parts, 280 parts, 300 parts, etc.

[0041] Potassium fluoroborate can be 1 to 4 parts, and in this content range it mainly acts as a flux. It can reduce the melting point and viscosity of the slag, making it easier for the coating to melt during welding and form a slag with good performance. This helps the formation and flow of slag during welding, ensuring that the slag can cover the molten pool in time and play its protective role. An appropriate amount of potassium fluoroborate can adjust the interface properties between the slag and the weld metal, making it easier for the slag to separate from the weld surface after welding is completed, which helps to obtain a weld with better appearance quality. Exemplarily, the potassium fluoroborate can be 1 part, 2 parts, 3 parts, 4 parts, etc.

[0042] Sodium alginate can be 1 to 15 parts, and sodium alginate is used as a binder. Within the content range of 1 to 15 parts, it can make the coating well coated on the welding core. In the manufacturing process of the welding rod, sodium alginate ensures that the coating components are closely combined and firmly attached to the surface of the welding core. In this way, during the welding process, the coating will not fall off easily, maintaining the integrity of the coating, thereby ensuring that the various components in the coating can play a normal role. And sodium alginate ensures the stability of the coating, so that the welding rod can continue to play a role stably during use. Exemplarily, the sodium alginate can be 1 part, 2 parts, 3 parts, 5 parts, 7 parts, 9 parts, 11 parts, 13 parts, 15 parts, etc.

[0043] The amount of soda ash can be 5 to 10 parts. The main function of soda ash (sodium carbonate) is to adjust the pH of the coating. Appropriate pH has an important influence on the reaction of various components in the coating and the performance of the slag. Participating in slag formation reactions: Soda ash may participate in some slag formation reactions, interact with other components (such as dolomite, magnesite, etc.), and jointly affect the performance of the slag. In this way, it also indirectly affects the quality of the weld, such as improving the protective effect of the slag on the molten pool and reducing the occurrence of weld defects. Exemplarily, the soda ash can be 5 parts, 6 parts, 7 parts, 8 parts, 9 parts, 10 parts, etc.

[0044] In addition, dolomite: CaCO 3 ≥50%、MgCO 3 ≥40%, S≤0.03%, P≤0.03%, particle size requirements are: -40 mesh: ≥100%, -150 mesh: ≤60%; lithium carbonate: Li 2 CO 3 ≥99.5%, particle size requirement: -40 mesh: ≥100%; barium carbonate: BaCO 3 ≥99.5%, particle size requirement: -40 mesh: ≥100%; magnesia: MgCO 3 ≥95%, S≤0.01%, P≤0.02%, particle size requirements are: -40 mesh: ≥100%, -150 mesh: ≤60%; Fluorite: CaF 2 ≥98%、SiO2 ≤1.0%, C≤0.05%, S≤0.01%, P≤0.02%, particle size requirements are: -40 mesh: ≥100%, -150 mesh: ≤60%; Ferrosilicon: Si: 42%-47%, S≤0.02%, P≤0.03%, particle size requirements -40 mesh: ≥100%; Nickel powder: Ni≥99.8%, particle size requirements -60 mesh: 100%; Ferromolybdenum: Mo: 55%-60%, S≤0.02%, P≤0.03%, particle size requirements -60 mesh: ≥100%; Metallic chromium: Cr≥99.9%, particle size requirements -60 mesh: 100%; Potassium fluoroborate: KBF 4 ≥99.9%, particle size requirement is: -40 mesh: ≥100%; aluminum-magnesium alloy: Al+Mg≥97.5%, Al: 47%-53%, particle size requirement is: -80 mesh: ≥95%.

[0045] In some embodiments, the chemical composition of the welding core includes: carbon, manganese, silicon, nickel, molybdenum, chromium, niobium, copper, sulfur, phosphorus, and matrix element Fe; wherein, in parts by mass,

[0046] Carbon is 0.07 to 0.12 parts, manganese is 0.90 to 1.50 parts, silicon is 0.05 to 0.10 parts, nickel is 0.50 to 1.00 parts, molybdenum is 0.01 to 0.10 parts, chromium is 0.01 to 0.10 parts, niobium is 0.01 to 0.10 parts, copper is 0.50 to 0.70 parts, sulfur is 0.001 to 0.005 parts, and phosphorus is 0.001 to 0.007 parts.

[0047] In the embodiments of the present application, the welding core provides the basic metal framework and some alloying elements, and the components in the coating further supplement and regulate the alloying components. For example, the alloying elements such as nickel powder, molybdenum iron, and metallic chromium in the coating, when combined with the original nickel, molybdenum, and chromium in the welding core, work together to make the weld alloying more precise and meet the complex and diverse performance requirements. The coating protects the molten pool through a series of metallurgical reactions such as slag making, deoxidation, and desulfurization, reducing impurities in the weld. The low sulfur and phosphorus content design of the welding core itself, combined with the purification function of the coating, greatly improves the purity of the weld, ensuring that the weld has higher strength, toughness, and crack resistance.

[0048] Carbon can be 0.07 to 0.12 parts, and carbon is a key element that affects the strength and toughness of steel. Within this content range, it can provide a certain strength to the welding core. Exemplarily, the carbon can be 0.07 parts, 0.08 parts, 0.09 parts, 0.10 parts, 0.11 parts, 0.12 parts, etc.

[0049] Manganese can be 0.90 parts to 1.50 parts. Manganese is an effective deoxidizer that can combine with oxygen in the weld to reduce the oxygen content and prevent defects such as pores. At the same time, manganese can also strengthen ferrite, improve the strength and toughness of the welding core, make the welding core less likely to deform or break when subjected to external force, and help the weld maintain good mechanical properties. Exemplarily, the manganese can be 0.90 parts, 1.0 parts, 1.10 parts, 1.20 parts, 1.30 parts, 1.40 parts, 1.50 parts, etc.

[0050] Silicon can be 0.05 to 0.10 parts. Silicon also has deoxidation ability. It reacts with oxygen to form silicon dioxide, which purifies the weld. An appropriate amount of silicon can also improve the fluidity of the welding core, allowing the molten metal to fill the gap of the base material more smoothly during the welding process, which is conducive to the formation of the weld and also helps to optimize the final mechanical properties of the welding core. Exemplarily, the silicon can be 0.05 parts, 0.06 parts, 0.07 parts, 0.08 parts, 0.09 parts, 0.10 parts, etc.

[0051] The nickel content can be 0.50 to 1.00 parts. After nickel is incorporated into the welding core, its toughness, especially low-temperature toughness, is significantly improved. For some welding structures that may serve in low-temperature environments, the presence of nickel can reduce the brittle transition temperature of the welding core, allowing the weld to maintain good impact resistance under low-temperature conditions and prevent brittle fracture. Exemplarily, the nickel content can be 0.50, 0.60, 0.70, 0.80, 0.90, 1.00, etc.

[0052] Molybdenum can be 0.01 to 0.10 parts. Molybdenum can refine the grains. The refined grain structure improves the strength and toughness of the welding core at the same time. In addition, molybdenum gives the welding core the property of resisting tempering softening. When it undergoes a subsequent heat treatment process, it can maintain good mechanical properties and ensure stable weld quality. Exemplarily, the molybdenum can be 0.01, 0.02, 0.04, 0.06, 0.08, 0.10, etc.

[0053] Chromium can be 0.01 to 0.10 parts, and chromium brings oxidation resistance and corrosion resistance to the welding core. When the welded parts need to be exposed to a certain corrosive environment, the dense oxide film formed by the chromium element can prevent the corrosion of external corrosive media and extend the service life of the weld and the weld as a whole. Exemplarily, the chromium can be 0.01 parts, 0.02 parts, 0.04 parts, 0.06 parts, 0.08 parts, 0.10 parts, etc.

[0054] Niobium can be 0.01 to 0.10 parts. Niobium is a strong carbide-forming element. It combines with carbon to form stable carbides, which can refine grains, play a dispersion strengthening effect, enhance the strength of the welding core, and inhibit grain growth, maintain the stability of the welding core microstructure, and improve the overall performance. Exemplarily, the niobium can be 0.01 parts, 0.02 parts, 0.04 parts, 0.06 parts, 0.08 parts, 0.10 parts, etc.

[0055] The copper content can be 0.50 to 0.70 parts. Copper helps improve the corrosion resistance of the welding core, especially in some weakly acidic or weakly alkaline corrosive environments. At the same time, copper can also strengthen the welding core to a certain extent, but excessive addition may cause hot brittleness, so it is more appropriate to limit it to this content range. Exemplarily, the copper can be 0.50 parts, 0.55 parts, 0.60 parts, 0.65 parts, 0.70 parts, etc.

[0056] Sulfur can be 0.001 to 0.005 parts. Sulfur is a harmful impurity. Even a small amount of it will cause hot brittleness of the welding core. Strictly controlling the sulfur content is to avoid the formation of low-melting eutectic with iron during welding hot working, which reduces the toughness and hot working performance of the welding core. Exemplarily, the sulfur can be 0.001, 0.002, 0.003, 0.004, 0.005, etc.

[0057] Phosphorus can be 0.001 to 0.007 parts. Phosphorus is also a harmful impurity. It will cause cold brittleness of the welding core, which greatly reduces the toughness of the welding core in a low temperature environment. Controlling the phosphorus content at a low level can ensure that the welding core and subsequent welds work normally under low temperature conditions. Exemplarily, the phosphorus can be 0.001 parts, 0.002 parts, 0.003 parts, 0.004 parts, 0.005 parts, 0.006 parts, 0.007 parts, etc.

[0058] In a second aspect, an embodiment of the present application provides a method for preparing the welding rod according to any one of the embodiments of the first aspect, Figure 1 A schematic diagram of a method for preparing a welding rod provided in an embodiment of the present application; see Figure 1 , the preparation method comprises:

[0059] S1, mixing the coating powder and the binder to obtain a mixed material;

[0060] S2. Performing a first baking, a second baking and cooling the mixed material in sequence to obtain a welding rod; wherein the temperature of the first baking is 85° C. to 90° C., and the temperature of the second baking is 380° C. to 400° C.

[0061] In some embodiments, the weight of the binder is 20% to 30% of the weight of the coating powder.

[0062] In some embodiments, the cooling end point temperature is ≤50°C.

[0063] In the embodiment of the present application, the binder binds these loose powders together to form a relatively stable whole. First baking (85℃~90℃): This stage belongs to low-temperature baking, the purpose of which is to preliminarily remove the moisture in the coating mixture. Second baking (380℃~400℃): This is a high-temperature baking link, which has two key functions. First, further deep drying the coating and completely removing the residual moisture, which is particularly important for ultra-low hydrogen coating electrodes, because moisture is an important source of hydrogen in the weld, and strict moisture control can greatly reduce the hydrogen content of the weld and reduce the risk of hydrogen-induced cracks. Second, high temperature promotes some pre-reactions between the coating powders, optimizes the fusion and interaction between the components, and allows the slag formation characteristics, alloy element transition ability and other properties to reach the best state during subsequent welding. Cooling (the end temperature is below 50℃): The cooling process is indispensable. It allows the coating baked at high temperature to cool down quickly, stabilize the internal structure and composition state, avoid excessive oxidation and degradation of the components due to long-term high temperature, and finally obtain a welding rod with excellent performance and stable quality. Exemplarily, the temperature of the first baking can be 85°C, 86°C, 87°C, 88°C, 89°C, 90°C, etc.; the temperature of the second baking can be 380°C, 390°C, 400°C, etc.; the terminal temperature of cooling can be 50°C, 49°C, 48°C, 47°C, etc.

[0064] The weight of the binder can be 20% to 30% of the weight of the coating powder. The coating powder is fully bonded to avoid the coating being loose and peeling during the electrode manufacturing process. At the same time, excessive binder may not be completely decomposed during the baking process. The residual binder components affect the metallurgical properties of the coating, interfere with the normal slag formation, alloy element transition and other reactions of the coating, and thus damage the quality of the electrode and weld. Exemplarily, the weight of the binder can be 20%, 22%, 24%, 26%, 28%, 30%, etc. of the weight of the coating powder.

[0065] The preparation method of the welding rod is implemented based on the above-mentioned welding rod. The specific chemical composition of the welding rod can refer to the above-mentioned embodiment. Since the preparation method of the welding rod adopts part or all of the technical solutions of the above-mentioned embodiments, it at least has all the beneficial effects brought by the technical solutions of the above-mentioned embodiments, which will not be described one by one here.

[0066] In a third aspect, an embodiment of the present application provides a 620 MPa grade cladding metal for welding a low alloy steel electrode with an ultra-low hydrogen coating for a generator set, wherein the cladding metal is obtained by the electrode described in any one of the first aspects during the welding process.

[0067] In the embodiment of the present application, if the diameter of the welding core is 3.2 mm, the welding current is 90A-120A, the welding voltage is 20V-25V, the welding speed is 150mm / min, and the interlayer temperature during welding is 90℃-110℃; if the diameter of the welding core is 4.0 mm, the welding current is 160A-180A, the welding voltage is 22V-30V, the welding speed is 150mm / min, and the interlayer temperature during welding is 90℃-110℃. Since a low-alloy steel electrode with ultra-low hydrogen coating is used, the coating composition is special and the welding process is strictly required. Accurate current, voltage, and speed control, combined with a specific interlayer temperature, can make the coating fully play its role. A stable arc ensures that the coating melts smoothly, releases alloy elements and accurately transitions to the deposited metal, and slag-forming components form high-quality slag to protect the molten pool; the appropriate interlayer temperature helps the slag to continuously cover and purify the molten pool, synergistically reduce the hydrogen content of the weld, improve crack resistance, and comprehensively guarantee the high quality of the welded plate. Exemplarily, if the diameter of the welding core is 3.2 mm, the welding current can be 90A, 100, 110, 120A, etc., the welding voltage is 20V, 21V, 22V, 23V, 24V, 25V, etc., the welding speed can be 150mm / min, and the interlayer temperature during welding can be 90℃, 100℃, 110℃, etc. If the diameter of the welding core is 4.0 mm, the welding current can be 160A, 170, 180A, etc., the welding voltage is 22V, 23V, 24V, 25V, 26V, 27V, 28V, 29V, 30V, etc., the welding speed can be 150mm / min, and the interlayer temperature during welding can be 90℃, 100℃, 110℃, etc.

[0068] In some embodiments, the chemical composition of the deposited metal includes: carbon, manganese, silicon, nickel, molybdenum, chromium, niobium, copper, boron, aluminum, magnesium, sulfur, phosphorus, and matrix element Fe; wherein, in parts by mass,

[0069] Carbon is 0.07 to 0.12 parts, manganese is 0.90 to 1.50 parts, silicon is 0.15 to 0.30 parts, nickel is 0.80 to 1.40 parts, molybdenum is 0.30 to 0.60 parts, chromium is 0.10 to 0.30 parts, niobium is 0.01 to 0.10 parts, copper is 0.50 to 0.70 parts, boron is 0.0001 to 0.003 parts, aluminum is 0.0001 to 0.010 parts, magnesium is 0.0001 to 0.010 parts, sulfur is 0.001 to 0.005 parts, and phosphorus is 0.001 to 0.007 parts.

[0070] In the embodiment of the present application, the chemical composition of the deposited metal is jointly determined by the welding core and the coating. The alloying elements in the welding core will directly enter the deposited metal during the melting process, while the alloying elements in the coating will transition to the deposited metal through metallurgical reactions. The nickel powder, ferromolybdenum, metallic chromium and other components in the coating can supplement the deposited metal with elements such as nickel, molybdenum, and chromium to make their content reach the required range. At the same time, the deoxidizer (such as ferrosilicon, aluminum-magnesium alloy) in the coating can control the oxygen content in the deposited metal, and the desulfurizer can reduce the sulfur content, thereby ensuring the quality of the deposited metal.

[0071] In some embodiments, the diffusible hydrogen of the deposited metal is 0.5 ml / 100 g to 4.0 ml / 100 g, and the water content of the coating of the welding rod is 0.05% to 0.15%.

[0072] In some embodiments, the deposited metal satisfies the following mechanical properties: room temperature tensile strength of the weld is 620MPa~800MPa, room temperature yield strength is 530MPa~700MPa, room temperature elongation after break is 18%~35%, high temperature tensile strength of the weld at 400℃ is ≥500MPa, 0℃ impact single value is ≥100J, -40℃ impact single value is ≥60J, and the ductile-brittle transition temperature of the drop hammer test is ≤-10℃.

[0073] In the embodiment of the present application, the preheating and interlayer temperature of the welding rod weld is 90℃-110℃, and the heat treatment after the weld is completed is: maximum heat treatment 620℃×9h, minimum heat treatment 620℃×1h, the heating and cooling rates above 300℃ are 40℃ / h-100℃ / h, and the heating and cooling rates are not controlled below 300℃.

[0074] For example, the welding rod is mainly used for welding 15NiCuMoNb5-6-4 steel of steam and water supply loop equipment in conventional island of nuclear power plant and WB36 steel welds of high-parameter thermal power generation equipment. The main chemical composition of 15NiCuMoNb5-6-4 steel and welding rod deposited metal is shown in Table 1, and the main mechanical properties of 15NiCuMoNb5-6-4 steel and welding rod deposited metal are shown in Table 2.

[0075] Table 1 Main chemical compositions of 15NiCuMoNb5-6-4 steel and electrode deposited metal

[0076]

[0077] Table 2 Main mechanical properties of 15NiCuMoNb5-6-4 steel and electrode deposited metal

[0078]

[0079] In terms of chemical composition, the electrode deposited metal involved in the embodiment of the present application is similar to the main components of the matching parent material. The C content in the electrode deposited metal is appropriately reduced to improve its weldability, and an appropriate amount of trace alloys such as Cr and Mo are added to refine the grains and improve the mechanical properties of the weld. In terms of tensile strength: the electrode deposited metal involved in the embodiment of the present application is at the same level as steel. In terms of impact performance: the electrode deposited metal involved in the embodiment of the present application is slightly better than steel in design, and the weld metal can obtain better impact toughness performance.

[0080] The welding method is implemented based on the above-mentioned welding rod. The specific chemical composition of the welding rod can refer to the above-mentioned embodiment. Since the welding method adopts part or all of the technical solutions of the above-mentioned embodiments, it has at least all the beneficial effects brought by the technical solutions of the above-mentioned embodiments, which will not be described one by one here.

[0081] The present application will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are intended only to illustrate the present application and are not intended to limit the scope of the present application. The experimental methods for the unrecorded specific conditions in the following examples are usually measured according to national standards. If there is no corresponding national standard, then carry out according to general international standards, normal conditions or according to the conditions recommended by the manufacturer.

[0082] Example 1

[0083] A 620MPa-grade low-alloy steel welding rod with ultra-low hydrogen coating for generator sets, the welding rod comprises a welding core and a coating coated on the surface of the welding core, the coating composition and content of which are: 130 parts by weight of dolomite, 140 parts by weight of lithium carbonate, 280 parts by weight of barium carbonate, 150 parts by weight of magnesia, 310 parts by weight of fluorite, 120 parts by weight of ferrosilicon, 15 parts by weight of nickel powder, 15 parts by weight of ferromolybdenum, 6 parts by weight of metallic chromium, 2 parts by weight of potassium fluoroborate, 1 part by weight of aluminum-magnesium alloy, 5 parts by weight of sodium alginate, and 8 parts by weight of soda ash. The diameter of the welding core is 4.0 mm, and the length is processed to be 400 mm. The welding core comprises (wt%) 0.10% carbon, 1.40% manganese, 0.08% silicon, 0.85% nickel, 0.05% molybdenum, 0.02% chromium, 0.02% niobium, 0.65% copper, 0.003% sulfur, 0.005% phosphorus, and the remaining elements are iron and impurity elements.

[0084] A method for preparing a welding rod comprises: stirring and mixing a coating powder for 18 minutes, adding a binder (43° potassium sodium water glass) of 25% of the total coating, stirring and mixing for 8 minutes. The mixed powder is sent into an oil pump machine to be coated on a welding core. The welding rod is baked at a low temperature of 88°C for 2.5 hours, and then baked at a high temperature of 390°C for 1.5 hours. After the high temperature baking, the welding rod is cooled to 48°C to obtain a finished welding rod. The finished welding rod with a welding core diameter of 3.2 mm has a diameter of 5.20 mm, and the welding rod with a welding core diameter of 4.0 mm has a diameter of 6.60 mm. The welding rod is packaged. Pay attention to the temperature and humidity during storage. The indoor temperature is above 5°C, the relative humidity does not exceed 60%, and it is kept at a certain distance from the ground and the wall. The room is kept dry and clean, stored in categories, with clear signs, and no harmful media can be stored.

[0085] A welding method, comprising: welding conditions: the welding test plate is prepared according to the standard GB / T25774.1-2010 "Testing of welding materials Part 1: Preparation and testing of mechanical properties of steel, nickel and nickel alloy deposited metal specimens", the welding test plate thickness is 20mm, the test plate width is 150mm, and the test plate length is 400mm. The test plate preheating temperature before welding is 90℃, and the welding power supply adopts DC reverse connection. The specification of 3.2mm is welded from 1 layer to 3 layers, the welding current is 100A, the welding voltage is 23V, the welding speed is 150mm / min, and the interlayer temperature during welding is 100℃. The specification of 4.0mm is welded from 4 layers to 8 layers, the welding current is 170A, the welding voltage is 26V, the welding speed is 150mm / min, and the interlayer temperature during welding is 100℃. The total number of test plate welding layers is 8 layers. After the test plate is welded, it is cooled to room temperature and surface grinding is performed, and the surface is polished smooth and the test plate pad is processed before flaw detection.

[0086] The welding control technology test plate heat treatment and test items involved in the embodiment of the present application include: maximum heat treatment 620℃×9h, minimum heat treatment 620℃×1h, heating and cooling rates above 300℃ are 40℃ / h-100℃ / h, and heating and cooling rates are not controlled below 300℃. The test items are chemical composition analysis test, tensile test, impact test, drop hammer test, diffusible hydrogen test, and water content of electrode coating.

[0087] After welding: The chemical composition of the electrode deposited metal is: carbon 0.09%, manganese 1.25%, silicon 0.20%, nickel 1.25%, molybdenum 0.33%, chromium 0.15%, niobium 0.015%, copper 0.60%, boron 0.0004%, aluminum 0.005%, magnesium 0.0005%, sulfur 0.004%, phosphorus 0.006%, and the remaining elements are iron and impurity elements.

[0088] The mechanical properties of the weld (deposited metal) heat treated at 620℃×9h are: room temperature tensile strength of the weld 671MPa, room temperature yield strength 549MPa, room temperature elongation 20%, high temperature tensile strength of the weld 400℃ 544MPa, 0℃ impact 200J, 211J, 202J, -40℃ impact 120J, 131J, 132J, drop hammer test ductile-brittle transition temperature -25℃. The mechanical properties of the weld heat treated at 620℃×1h are: room temperature tensile strength of the weld 695MPa, room temperature yield strength 579MPa, room temperature elongation 20%, high temperature tensile strength of the weld 400℃ 577MPa, 0℃ impact 190J, 200J, 192J, -40℃ impact 100J, 101J, 112J, drop hammer test ductile-brittle transition temperature -20℃. The diffused hydrogen of the electrode deposited metal is 3.6ml / 100g, and the water content of the electrode coating is 0.12%.

[0089] Example 2

[0090] A 620MPa-grade low-alloy steel welding rod with ultra-low hydrogen coating for generator sets, the welding rod comprises a welding core and a coating coated on the surface of the welding core, the coating composition and content of which are: 180 parts by weight of dolomite, 130 parts by weight of lithium carbonate, 250 parts by weight of barium carbonate, 140 parts by weight of magnesia, 310 parts by weight of fluorite, 120 parts by weight of ferrosilicon, 15 parts by weight of nickel powder, 15 parts by weight of ferromolybdenum, 6 parts by weight of metallic chromium, 2 parts by weight of potassium fluoroborate, 1 part by weight of aluminum-magnesium alloy, 5 parts by weight of sodium alginate, and 8 parts by weight of soda ash. The diameter of the welding core is 4.0 mm, and the length is processed to be 400 mm. The welding core comprises (wt%) 0.10% carbon, 1.40% manganese, 0.08% silicon, 0.85% nickel, 0.05% molybdenum, 0.02% chromium, 0.02% niobium, 0.65% copper, 0.003% sulfur, 0.005% phosphorus, and the remaining elements are iron and impurity elements.

[0091] A method for preparing a welding rod comprises: stirring and mixing a coating powder for 18 minutes, adding a binder (43° potassium sodium water glass) of 25% of the total coating, stirring and mixing for 8 minutes. The mixed powder is sent into an oil pump machine to be coated on a welding core. The welding rod is baked at a low temperature of 88°C for 2.5 hours, and then baked at a high temperature of 390°C for 1.5 hours. After the high temperature baking, the welding rod is cooled to 48°C to obtain a finished welding rod. The finished welding rod with a welding core diameter of 3.2 mm has a diameter of 5.20 mm, and the welding rod with a welding core diameter of 4.0 mm has a diameter of 6.60 mm. The welding rod is packaged. Pay attention to the temperature and humidity during storage. The indoor temperature is above 5°C, the relative humidity does not exceed 60%, and it is kept at a certain distance from the ground and the wall. The indoor room is kept dry and clean, stored in categories, with clear signs and no harmful media can be stored.

[0092] A welding method, comprising: welding conditions: the welding test plate is prepared according to the standard GB / T25774.1-2010 "Testing of welding materials Part 1: Preparation and testing of mechanical properties of steel, nickel and nickel alloy deposited metal", the welding test plate thickness is 20mm, the test plate width is 150mm, and the test plate length is 400mm. Please refer to the following welding scheme 1 and welding scheme 2.

[0093] Welding solution 1

[0094] Before welding, the test plate was preheated to 90°C, the welding power supply was reversed DC, the specification was 3.2 mm, the welding current was 100A, the welding voltage was 23V, the welding speed was 150mm / min, the interlayer temperature during welding was 100°C, and the total number of test plate welding layers was 9. After the test plate was welded, it was cooled to room temperature and surface polished. After the surface was polished smooth and the test plate pad was processed, flaw detection was performed.

[0095] The welding control technology test plate heat treatment and test items involved in the embodiment of the present application include: maximum heat treatment 620℃×9h, minimum heat treatment 620℃×1h, heating and cooling rates above 300℃ are 40℃ / h-100℃ / h, and heating and cooling rates are not controlled below 300℃. The test items are chemical composition analysis test, tensile test, impact test, drop hammer test, diffusible hydrogen test, and water content of electrode coating.

[0096] The chemical composition of the electrode deposited metal is: 0.087% carbon, 1.15% manganese, 0.19% silicon, 1.27% nickel, 0.34% molybdenum, 0.16% chromium, 0.017% niobium, 0.61% copper, 0.0004% boron, 0.005% aluminum, 0.0005% magnesium, 0.003% sulfur, 0.006% phosphorus, and the remaining elements are iron and impurity elements.

[0097] The mechanical properties of the weld (deposited metal) heat treated at 620℃×9h are: room temperature tensile strength of the weld 669MPa, room temperature yield strength 570MPa, room temperature elongation 22%, high temperature tensile strength of the weld 400℃ 540MPa, 0℃ impact 220J, 221J, 209J, -40℃ impact 140J, 137J, 133J, drop hammer test ductile-brittle transition temperature -25℃. The mechanical properties of the weld heat treated at 620℃×1h are: room temperature tensile strength of the weld 690MPa, room temperature yield strength 575MPa, room temperature elongation 21%, high temperature tensile strength of the weld 400℃ 575MPa, 0℃ impact 195J, 185J, 190J, -40℃ impact 110J, 121J, 116J, drop hammer test ductile-brittle transition temperature -20℃.

[0098] Welding solution 2

[0099] Before welding, the test plate preheating temperature is 90℃, the welding power supply adopts DC reverse connection, the specification is 4.0 mm welding, the welding current is 170A, the welding voltage is 26V, the welding speed is 150mm / min, and the interlayer temperature during welding is 100℃. The total number of test plate welding layers is 7. After the test plate is welded, it is cooled to room temperature and the surface is polished. After the surface is polished smooth and the test plate pad is processed, flaw detection is performed.

[0100] The welding control technology test plate heat treatment and test items involved in the embodiment of the present application include: maximum heat treatment 620℃×9h, minimum heat treatment 620℃×1h, heating and cooling rates above 300℃ are 40℃ / h-100℃ / h, and heating and cooling rates are not controlled below 300℃. The test items are chemical composition analysis test, tensile test, impact test, drop hammer test, diffusible hydrogen test, and water content of electrode coating.

[0101] The chemical composition of the electrode deposited metal is: 0.10% carbon, 1.30% manganese, 0.23% silicon, 1.31% nickel, 0.36% molybdenum, 0.17% chromium, 0.016% niobium, 0.62% copper, 0.0004% boron, 0.004% aluminum, 0.0004% magnesium, 0.005% sulfur, 0.005% phosphorus, and the remaining elements are iron and impurity elements.

[0102] The mechanical properties of the weld (deposited metal) heat treated at 620℃×9h are: room temperature tensile strength of the weld 680MPa, room temperature yield strength 579MPa, room temperature elongation 20%, high temperature tensile strength of the weld 400℃ 589MPa, 0℃ impact 200J, 191J, 189J, -40℃ impact 90J, 97J, 93J, drop hammer test ductile-brittle transition temperature -20℃. The mechanical properties of the weld heat treated at 620℃×1h are: room temperature tensile strength of the weld 700MPa, room temperature yield strength 605MPa, room temperature elongation 19%, high temperature tensile strength of the weld 400℃ 601MPa, 0℃ impact 175J, 165J, 170J, -40℃ impact 80J, 81J, 86J, drop hammer test ductile-brittle transition temperature -15℃. The diffused hydrogen of the electrode deposited metal is 3.4ml / 100g, and the water content of the electrode coating is 0.11%.

[0103] One or more technical solutions in the embodiments of the present application also have at least the following technical effects or advantages:

[0104] (1) The welding rod provided in the embodiment of the present application has stable arc during welding, beautiful shape, good crack resistance of the weld metal of the welding rod, and the weld metal has chemical composition and mechanical properties equivalent to those of steel. It can replace foreign welding rods for welding 15NiCuMoNb5-6-4 steel for steam and water supply loop equipment in conventional nuclear power islands and WB36 steel welds for high-parameter thermal power generation equipment. The localization of the welding rod can also reduce the cost of the manufacturing plant and shorten the procurement cycle, which is conducive to cost saving.

[0105] The above description is only a specific implementation of the present application, so that those skilled in the art can understand or implement the present application. Various modifications to these embodiments will be apparent to those skilled in the art, and the general principles defined herein can be implemented in other embodiments without departing from the spirit or scope of the present application. Therefore, the present application will not be limited to the embodiments shown herein, but will conform to the widest range consistent with the principles and novel features applied for herein.

Claims

1. A 620MPa grade low alloy steel welding rod with ultra-low hydrogen coating for a generator set, the welding rod comprising a welding core and a coating covering at least a portion of the surface of the welding core, the chemical composition of the coating comprising: Dolomite, lithium carbonate, barium carbonate, magnesite, fluorite, ferrosilicon, nickel powder, ferromolybdenum, metallic chromium, potassium fluoroborate, aluminum-magnesium alloy, sodium alginate and soda ash; wherein, in parts by mass, Dolomite is 100 to 200 parts, lithium carbonate is 100 to 150 parts, magnesite is 100 to 200 parts, fluorite is 300 to 350 parts, ferrosilicon is 100 to 150 parts, nickel powder is 10 to 20 parts, ferromolybdenum is 10 to 20 parts, metallic chromium is 5 to 10 parts, and aluminum-magnesium alloy is 1 to 3 parts.

2. The welding rod according to claim 1, characterized in that The barium carbonate is 200 to 300 parts, the potassium fluoroborate is 1 to 4 parts, the sodium alginate is 1 to 15 parts, and the soda ash is 5 to 10 parts.

3. The welding rod according to claim 1 or 2, characterized in that: The chemical composition of the welding core includes: carbon, manganese, silicon, nickel, molybdenum, chromium, niobium, copper, sulfur, phosphorus, and matrix element Fe; wherein, in parts by mass, Carbon is 0.07 to 0.12 parts, manganese is 0.90 to 1.50 parts, silicon is 0.05 to 0.10 parts, nickel is 0.50 to 1.00 parts, molybdenum is 0.01 to 0.10 parts, chromium is 0.01 to 0.10 parts, niobium is 0.01 to 0.10 parts, copper is 0.50 to 0.70 parts, sulfur is 0.001 to 0.005 parts, and phosphorus is 0.001 to 0.007 parts.

4. A method for preparing the welding rod according to any one of claims 1 to 3, the method comprising: Mixing the coating powder with the binder to obtain a mixed material; The mixed material is sequentially subjected to a first baking, a second baking and cooling to obtain a welding rod; wherein the temperature of the first baking is 85°C to 90°C, and the temperature of the second baking is 380°C to 400°C.

5. The preparation method according to claim 4, characterized in that: The weight of the binder is 20% to 30% of the weight of the coating powder.

6. The preparation method according to claim 4, characterized in that: The cooling end point temperature is ≤50°C.

7. A 620MPa grade cladding metal for welding low alloy steel electrodes with ultra-low hydrogen coating for power generation sets, wherein the cladding metal is obtained during the welding process of the electrode according to any one of claims 1 to 3.

8. The cladding metal according to claim 7, characterized in that: The chemical composition of the deposited metal includes: carbon, manganese, silicon, nickel, molybdenum, chromium, niobium, copper, boron, aluminum, magnesium, sulfur, phosphorus, and matrix element Fe; wherein, in parts by mass, Carbon is 0.07 to 0.12 parts, manganese is 0.90 to 1.50 parts, silicon is 0.15 to 0.30 parts, nickel is 0.80 to 1.40 parts, molybdenum is 0.30 to 0.60 parts, chromium is 0.10 to 0.30 parts, niobium is 0.01 to 0.10 parts, copper is 0.50 to 0.70 parts, boron is 0.0001 to 0.003 parts, aluminum is 0.0001 to 0.010 parts, magnesium is 0.0001 to 0.010 parts, sulfur is 0.001 to 0.005 parts, and phosphorus is 0.001 to 0.007 parts.

9. The cladding metal according to claim 7, characterized in that: The diffusible hydrogen of the deposited metal is 0.5ml / 100g-4.0ml / 100g, and the water content of the coating of the welding rod is 0.05%-0.15%.

10. The cladding metal according to claim 7, characterized in that: The deposited metal meets the following mechanical properties: the room temperature tensile strength of the weld is 620MPa~800MPa, the room temperature yield strength is 530MPa~700MPa, the room temperature elongation after fracture is 18%~35%, the high temperature tensile strength of the weld at 400℃ is ≥500MPa, the single impact value at 0℃ is ≥100J, the single impact value at -40℃ is ≥60J, and the ductile-brittle transition temperature of the drop hammer test is ≤-10℃.

Citation Information

Patent Citations

  • Welding rod containing low temperature steel containing Ni

    CN103921017A

  • Ultralow-hydrogen low-alloy steel electrode for low-temperature steel

    CN104128717A

  • Special heat-resistant steel electrode suitable for 550 DEG C high-temperature work equipment pieces and preparation method thereof

    CN105252161A

  • 1100Mpa grade high-strength high-toughness low-alloy steel electric welding rod

    CN106425163A

  • High-performance weather-resistance welding rod for coating-free weather-resistance bridge steel

    CN110802343A